De las ruinas de los imperios : la rebelión contra Occidente y la metamorfosis de Asia - Mishra, Pankaj (Serie Actualidad (Galaxia Gutenberg (Firm)), 2014)
Provides an overview of the great thinkers and philosophical leaders from across Asia who helped change and shape the modern continent, including Tagore and Gandhi in India, Liang Qichao in China and Abdurreshi al Ibrahim in the Ottoman Empire.